Problematika Pendidikan Islam Perspektif MaqÃ¢á¹£id SharÃ®Ê»ah - Rosidin, Rosidin (Koordinatorat Perguruan Tinggi Agama Islam Swasta Wilayah IV Surabaya, 2016)
The article seeks to reveal problems faced by Islamic education from the perspective of MaqÃ¢á¹£id al-SharÃ®Ê»ah, namely ideological (á¸¥ifáº al-dÃ®n), practical (á¸¥ifáº al-nafs), academic (á¸¥ifáº al-âaql), relationships or networks (á¸¥ifáº al-nasl), vocational (á¸¥ifáº al-mÃ¢l) and quality (á¸¥ifáº al-âirá¸) aspects. In order to know the details of crucial problems of the Islamic education along with their alternative solutions, this paper suggests that the Islamic education should consider the insiderâs and outsiderâs perspective which has four types of roles as follow: a) complete observer; b) observer as participant; c) participant as observer; d) complete participant. This article proposes three important implications, are: first, the problems of the Islamic education can be categorized and mapped based on MaqÃ¢á¹£id al-SharÃ®Ê»ah, in order to ease the analysis of such problems. Second, the analysis of the problems should be based on the insidersâ and outsidersâ point of views, so that it would be able to comprehensively detect the problems of Islamic education and show the inclusiveness of the Islamic education. Third, problem solving alternatives should be oriented at the level of theological (faith and religious [Ã®mÃ¢n]), theoretical (philosophical and empirical [âilm]), practical (learning and teaching [âamal]) and moral (ethics and aesthetics [akhlÃ¢q]) realms.Â